Navy Sea Ice Prediction Systems - Preller, Ruth H.; Posey, Pamela G.; Maslowksi, Wieslaw; Stark, Donald; Pham, Thomas T. C. (2002)
The availability of real-time information on sea ice conditions in ice covered seas has always been important, not only to strategic military operations, but to the economies of those countries that border the Arctic and its marginal seas. Knowledge of the thickness and movement of sea ice as well as the locations of open water is required for traversing the Arctic whether in a drill ship, in a cargo vessel or in an ice strengthened ship such as a Coast Guard ice breaker. Pub. in Jnl. of Oceanography, v15 n1 p44-56, 2002. Sponsored in part by Naval Space and Warfare Systems Command, Program Element 603207N.